Ectopic RNF168 expression promotes break-induced replication-like DNA synthesis at stalled replication forks. Issue 8 (17th March 2020) - Krais, John J; Johnson, Neil
Abstract: The RNF168 E3 ubiquitin ligase is activated in response to double stranded DNA breaks (DSBs) where it mono-ubiquitinates γH2AX (ub-H2AX). RNF168 protein expression and ubiquitin signaling are finely regulated during the sensing, repair and resolution of DNA damage in order to avoid excessive spreading of ubiquitinated chromatin. Supra-physiological RNF168 protein expression levels have been shown to block DNA end resection at DSBs and increase PARP inhibitor (PARPi) sensitivity. In this study, we examined the impact of ectopic RNF168 overexpression on hydroxyurea (HU)-induced stalled replication forks in the setting of BRCA1 deficiency. Surprisingly, RNF168 overexpression resulted in the extension of DNA fibers, despite the presence of HU, in BRCA1 deficient cells. Mechanistically, RNF168 overexpression recruited RAD18 to ub-H2AX at HU-induced DNA breaks. Subsequently, a RAD18-SLF1 axis was responsible for initiating DNA synthesis in a manner that also required the break-induced replication (BIR) factors RAD52 and POLD3. Strikingly, the presence of wild-type BRCA1 blocked RNF168-induced DNA synthesis. Notably, BIR-like repair has previously been linked with tandem duplication events found in BRCA1 -mutated genomes. Thus, in the absence of BRCA1, excessive RNF168 expression may drive BIR, and contribute to the mutational signatures observed in BRCA1 -mutated cancers.